Neuroglobin and Prolactin As Potential Biomarkers for Differentiating Epileptic versus Nonepileptic Paroxysmal Disorders in Children - Mahgoob, Mohammed Hashem; Moussa, Mahmoud Mohammed (Journal of Pediatric Epilepsy, 2020)
At least 20% of patients referred to pediatric epilepsy centers with the suspicion of epileptic seizures actually have other conditions. Neuroglobin is a new globin member which is highly expressed in the central and peripheral nervous systems. In this article, we aimed to evaluate usefulness of neuroglobin to differentiate between epilepsy and other conditions that mimic epilepsy. Our study was conducted on 90 children divided into three groups: 30 patients with epileptic seizures, 35 children with nonepileptic paroxysmal disorder, and 25 apparently healthy, age and sex-matched children as a normal control. Complete blood count, blood chemistries including random blood glucose, calcium, sodium, in addition to serum prolactin, and neuroglobin were performed for all children. This study showed a significant increase of both serum neuroglobin and prolactin levels in epileptic group compared with nonepileptic paroxysmal disorder and control groups (p < 0.01). Serum neuroglobin showed 95% sensitivity and 95.7% specificity in the diagnosis of generalized seizures. Serum neuroglobin may be a promising novel marker to differentiate epileptic versus nonepileptic disorders in children in the emergency setting, when history and clinical presentation are equivocal.
Keywords: neuroglobin; prolactin; nonepileptic disorders